Does trading by small investors improve or deteriorate price efficiency? Evidence from the minimum trade unit changes on the Korea exchange - Hee-joon Ahn (International Journal of Financial Studies, 2014)
In this study, we investigate the effect of minimum trade unit (MTU) reductions on the Korea Exchange (KRX) on price efficiency. The KRX switched its MTU from 10 shares to one share for high-price stocks twice, once in December 2004 and once in July 2006. The MTU changes were intended to attract small individual investors to the markets for high-price stocks. The MTU reductions on the KRX are different from previous cases of MTU reductions in other markets in that the KRX MTU reductions are not chosen by firms but are mandated by the exchange. Using these rare events, we examine whether the reductions in MTU and ensuing small investor participation enhance or deteriorate price efficiency. We examine three variables as indicators of price efficiency: return volatility, residual volatility, and the half-life of return volatility shock estimated from a generalized autoregressive conditional heteroskedasticity (GARCH) model. We find evidence of improved price efficiency from the 2004 event. For the 2004 sample, both return variance and residual return variance declined significantly after the MTU reduction. We also find evidence of reduction, albeit weak, in the half-life of volatility shock for the same sample. Meanwhile, for the 2006 sample, we do not find any changes in return variance or residual variance, nor do we find any evidence of change in the half-life of volatility shock. The difference in the patterns of changes in variables between the 2004 and 2006 events appears to be attributable to differences in the price levels of the stocks that were affected by the MTU changes and, consequently, a difference in reactions by small investors.
Keywords: G10; G28; 330; minimum trade unit; small investor participation; price efficiency; Korea Exchange